2020
DOI: 10.1186/s40359-020-0380-2
|View full text |Cite
|
Sign up to set email alerts
|

Treating medically unexplained symptoms via improving access to psychological therapy (IAPT): major limitations identified

Abstract: Background: Improving Access to Psychological Therapies is a UK Government funded initiative to widen access to psychological treatment for a range of common mental health complaints, such as depression and anxiety. More recently, the service has begun to treat patients with medically unexplained symptoms. This paper reports on a review of treatment protocols and early treatment data for medically unexplained symptoms, specifically the illness myalgic encephalomyelitis/chronic fatigue syndrome. Main text: A se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 67 publications
0
13
0
Order By: Relevance
“…Patients with PPS report more social isolation, psychological distress, more functional and occupational impairment, poorer quality of life and overall impaired health status in comparison to general practice patients not meeting the criteria for PPS (Creed et al, 2012 ; Dirkzwager & Verhaak, 2007 ; Woo, 2010 ). Depression and anxiety are common in patients with PPS (Burton et al, 2011 ) and are indicators of improvement in recovery (Geraghty & Scott, 2020 ). Accordingly, developing better management strategies for patients with PPS is a health care priority.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PPS report more social isolation, psychological distress, more functional and occupational impairment, poorer quality of life and overall impaired health status in comparison to general practice patients not meeting the criteria for PPS (Creed et al, 2012 ; Dirkzwager & Verhaak, 2007 ; Woo, 2010 ). Depression and anxiety are common in patients with PPS (Burton et al, 2011 ) and are indicators of improvement in recovery (Geraghty & Scott, 2020 ). Accordingly, developing better management strategies for patients with PPS is a health care priority.…”
Section: Discussionmentioning
confidence: 99%
“…In respect of humility, it is also pertinent that MUS research indicates that some patients value practitioners admitting that they do not know, rather than pretending otherwise (Kornelsen et al, 2016;Sharma et al, 2020). Finally, humility holds that non-medically trained practitioners should be cognisant of their training limitations (Geraghty & Scott, 2020) and should encourage the patient to consult with medical professionals in cases of doubt, rather than ascribing all manner of somatic symptoms to psychosocial causes.…”
Section: Resisting Biopsychosocial Hegemonymentioning
confidence: 99%
“…In terms of future research directions, there is a need to explore the experiences of people labelled with MUS in psy settings; in particular, the high drop-out rates amongst people labelled with MUS referred to IAPT (Geraghty & Scott, 2020) are of interest.…”
Section: Resisting Biopsychosocial Hegemonymentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effect sizes have remained rather moderate and the information on factors explaining the variability of individuals´ responses to treatment is scarce (Kleinstauber et al, 2011;van Dessel et al, 2014). It has also been suggested that the rationale behind the psychosocial treatments remains unclear for the patients and thus results in unwanted effects such as withdrawal from the treatment (Geraghty and Scott, 2020). To respond to these challenges some studies have suggested that tailoring treatments according to personalized profiles might improve the effectiveness (Rosmalen et al, 2020;Senger et al, 2021a,b).…”
Section: Introductionmentioning
confidence: 99%